Review on 3D audio technology - YIN Fu-liang; WANG Lin; CHEN Zhe (Tongxin xuebao)
The principle of 3D audio technology is introduced.The application of signal processing methods is reviewed in 3D audio from the measurement,computation,interpolation,approximation of head-related transfer functions（HRTF） and the methods for crosstalk cancellation.Finally,crrently hot topics in this area are summarized and the future research trends of 3D audio are discussed.